Mechanical models for the adhesive friction of nano- and micro-particles. (November 2021) - Huang, Gan-Yun; Li, Yi-Ran
Abstract: Friction is common in human's daily life and production that may be either detrimental or beneficial. The friction law at microscale or even smaller scales nevertheless is lacking. In the present work, on the basis of JKR model for adhesive contact and by analogy with the emission of dislocations at a crack tip, the critical tangential force has been obtained for the onset of sliding. When the tangential force in adhesive contact induces a torque at the interface, a mechanical model for rolling adhesion has been presented on the basis of the assumption that it is governed by adhesion hysteresis. The critical torque and tangential force for rolling onset have been determined, which may be taken as measure for the rolling friction force. Comparisons with relevant experiments and models have been made to support the present concept. A kind of friction duality in small sized particles can thus be predicted. Highlights: New models for sliding and rolling friction with the effect of adhesion have been established. Sliding friction is achieved through considering nucleation of interfacial dislocations and rolling friction achieved through introducing adhesion hysteresis. Agreement between the model results for sliding friction with some available experiments and atomistic results has been found. Friction duality may be found when comparing the sliding friction and rolling friction as a function of particle radius.